The Transformation of the Independent Curriculum in Madrasas and Its Implications for Learning Quality - Aida (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
Education is an essential factor that can determine a country's progress; on the other hand, an effective curriculum is necessary to produce a high-quality generation. Curriculum transformation is one of the strategic efforts in responding to the dynamics of education in the Merdeka Belajar era, including in basic and secondary education settings. The transformation of the Merdeka Curriculum in madrasas at the primary and secondary levels represents a strategic response to the dynamics of education in the Merdeka Belajar era, as regulated in Ministry of Education Regulation No. 1 of 2026. This study aims to examine how the Merdeka Curriculum transformation is implemented in madrasas and its implications for the quality of learning. The method used is qualitative with a literature study approach by reviewing various relevant scientific sources. The findings show that the transformation of the madrasa curriculum is characterized by flexibility in the learning process and the strengthening of student-centered learning. The implications of this transformation are reflected in the improvement of learning quality, as seen in students' active participation and teachers' creativity in designing more contextual learning models. However, the main challenges include human resource readiness and infrastructure availability. These implications recommend continuous teacher training and principal evaluation to optimize the implementation of the Merdeka Curriculum.